PEMBERIAN PUPUK ANORGANIK DAN VERMIKOMPOST UNTUK PERTUMBUHAN KEDELAI DI TANAH PASANG SURUT: Application of Anorganic Fertilizer and Vermicompost for Soybean Growth In Tidal Soil - Muhammad Mustaanullah; Dedik Budianta; Adipati Napoleon (AgriPeat, 2022)
This study aims to determine the location-specific dosage of anorganic fertilization combined with vermicompost to increase the productivity of soybean in a tidal soil. This research was a pot experiment carried out in the Experimental Garden Agrotech Traning Center, Faculty of Agriculture, Sriwijaya University, Indralaya. This research was conducted in September 2019 to February 2020. The experimental method used was a factorial randomized block design with two factors, the first factor was the dosage of anorganic fertilizer which was dosage of fertilizer recommended by the South Sumatra Agricultural Research and Development Agency (D1) and , Site specific fertilizer dosage (D2), The second factor was vermicompost consisted of three levels, which were 5 tons ha-1 (V1), 7.5 tons ha-1 (V2) and 10 tons ha-1 (V3). Each treatment was made 3 replications. Hence, the total of treatments was 18 units. The variables observed were soil pH, N-total, P-available, K-dd and texture, and soil pH, N-total, and K-dd at primodial phase), the analysis of plants tissues were N and K, and plant growth consisted of plant height, number of seeds per plant, number of pod contents, weight of 100 seeds and production. The results showed that location-specific fertilizer was the approppriate dose for soybean growth in tidal soil with a production of 1.18 tons ha-1, vermicompost at 7.5 tons ha-1 was obtained the highest yield with value of 1.30 tons ha-1 and a combination of site-specific fertilizerand vermicompost at 7.5 tons ha-1 was found the soybean yield with value of 1.47 tons ha-1